2011
DOI: 10.1111/j.1469-8986.2011.01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional arousal modulates the encoding of crime‐related details and corresponding physiological responses in the Concealed Information Test

Abstract: Previous studies demonstrated that concealed crime-related memories can be validly identified using the Concealed Information Test (CIT). However, its field applicability is still debated, and it is specifically unknown how emotional arousal during a crime would influence CIT results. In the current study, emotional arousal during a mock crime and the time delay between mock crime and CIT examination were manipulated. At the immediate and the delayed CIT occasion, central crime details were better remembered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 53 publications
3
45
1
1
Order By: Relevance
“…In Experiment 2, the difference was much less pronounced: Only 1.15 points, representing a moderate effect. The data indicate that pronounced differences in item saliency affect the validity of RT-based memory detection and thereby extend item saliency effects from physiological measures (Carmel, Dayan, Naveh, Raveh, & Ben-Shakhar, 2003;Gamer & Berti, 2012;Gamer, Kosiol, & Vossel, 2010;Jokinen et al, 2006;Lieblich et al, 1976;Nahari & Ben-Shakhar, 2011;Peth, Vossel, & Gamer, 2012) to RTs. We think that the 21 use of an independent assessment of item saliency will be of great use in future research.…”
Section: Item Saliencymentioning
confidence: 63%
“…In Experiment 2, the difference was much less pronounced: Only 1.15 points, representing a moderate effect. The data indicate that pronounced differences in item saliency affect the validity of RT-based memory detection and thereby extend item saliency effects from physiological measures (Carmel, Dayan, Naveh, Raveh, & Ben-Shakhar, 2003;Gamer & Berti, 2012;Gamer, Kosiol, & Vossel, 2010;Jokinen et al, 2006;Lieblich et al, 1976;Nahari & Ben-Shakhar, 2011;Peth, Vossel, & Gamer, 2012) to RTs. We think that the 21 use of an independent assessment of item saliency will be of great use in future research.…”
Section: Item Saliencymentioning
confidence: 63%
“…Also, as the test usually takes place weeks and sometimes months or even years after the crime, it is doubtful whether all crime-related items will be remembered during the test. Indeed, several recent laboratory studies using ANS measures revealed that, when the CIT is administered 1 or 2 weeks after the mock crime, certain critical items are not recalled and fail to elicit differential responses (Carmel, Dayan, Naveh, Raveh, & Ben-Shakhar, 2003;Gamer, Kosiol, & Vossel, 2010;Nahari & Ben-Shakhar, 2011;Peth, Vossel, & Gamer, 2012). Needless to say, the problem of false negatives caused by presenting critical details that are not remembered by the suspect will not be resolved by changing from ANS to P300 or fMRI measures.…”
Section: From the Lab To The Fieldmentioning
confidence: 99%
“…Third, recently Peth et al (2012) manipulated the level of stress during mock-crime execution and found that level of stress did not affect the relative responses to the critical CIT items with electrodermal, respiration, and cardiovascular measures. Furthermore, the data revealed that under the high arousal level, detection efficiency based on central items tended to be unaffected by delaying the test.…”
Section: Weaknesses and Potential Limitations Of The Citmentioning
confidence: 99%
“…Furthermore, the data revealed that under the high arousal level, detection efficiency based on central items tended to be unaffected by delaying the test. The authors concluded that, “emotional arousal might facilitate the detection of concealed information sometime after the crime occurred” (Peth et al, 2012, p. 381).…”
Section: Weaknesses and Potential Limitations Of The Citmentioning
confidence: 99%